Wave-based liquid-interface metamaterials - N Francois (Nature Portfolio, 2017)
Here, Francoiset al. propose a method of remotely shaping particle trajectories by using rotating waves on a liquid gas interface. The superposition of orthogonal standing waves creates angular momentum which is transferred from waves to floating microparticles, guiding them along closed trajectories.